Many Voices, Many Worlds : critical perspectives on community media in India - Ullah, Faiz 1982-; Monteiro, Anjali 1955-; Jayasankar, K. P 1952- (New Delhi : SAGE Publications India Pvt Ltd, 2021)
"This book brings together different forms and modalities of Community Media - such as video, radio, theatre, ICTs and new media - into a productive conversation with each other. It focuses on how the politics of caste, class, gender, and access to funding and technology, come to bear upon communities and their communicative practices"--
This book explores different forms of Community Media, focusing on how the politics of caste, class, gender, and access to funding and technology, come to bear upon communities and their communicative practices.
Keywords: Local mass media -- India. -- India -- Social conditions. -- Médias locaux -- Inde